Undocumented Children: KRI Tawau's Strategy in Facilitating Early Identity for Indonesian Migrant Workers' Children - Ariani, Fani; Koeswara, Hendri; Aromatica, Desna (Pencerah, 2025)
This study examines the strategies employed by the Consulate of the Republic of Indonesia (KRI) in Tawau to assist the children of Indonesian migrant workers (PMI) in Sabah’s palm oil plantations in obtaining birth identity documents—a crucial requirement for citizenship status and access to basic social services. Using a descriptive qualitative approach, data were collected through a literature review and in-depth interviews with consular officers and PMI families. The findings show that KRI Tawau has established a vision, mission, and objectives consistent with its mandate to protect Indonesian citizens abroad, particularly in securing the identity rights of migrant children. The Consulate implements outreach strategies, including public awareness campaigns on the importance of the Surat Bukti Pencatatan Kelahiran (SBPK), mobile consular services, and community-based cooperation, to reach families in remote plantation areas. These efforts have improved public awareness and expanded service coverage, although challenges persist, especially the incomplete administrative documents often held by migrant workers. Despite these constraints, KRI Tawau’s strengthened consular functions play a vital role in enhancing children’s access to identity documentation and improving their opportunities to obtain education, which remain limited under Malaysia’s migration and education policies. The study highlights the need for innovative and sustained consular services to protect the rights of migrant children.